THE PHENOMENON OF THE REIGN OF FEMALE PHARAOHS HATSHEPSUT AND TAUSERT. LEGITIMATION OF POWER - Бондаренко, Наталія (Київський національний університет імені Тараса Шевченка, 2023)
Introduction. This article explores the phenomenon of female pharaohs' reign in Ancient Egypt, focusing on the rule of Hatshepsut and Tausert during the New Kingdom. The research delves into the historical context, cultural significance, and peculiarities of power legitimization during their reigns. By analyzing primary sources, including inscriptions, statues, and archaeological artifacts, this study aims to shed light on the unique circumstances that allowed these women to ascend the throne in a society traditionally dominated by men. The accession of Queen Hatshepsut, 18th Dynasty, challenged prevailing expectations, which required the use of various additional instruments to legitimize her power: adopting male portrayals, emphasizing divine lineage, implementing an extensive building program, military and trade expeditions, and more. Later, Queen Tausert, 19th Dynasty, who ruled during a period of political turmoil and decline, employed similar strategies. Tausert's reign serves as a contrasting example, characterized by her association with her deceased husband, Seti II, as a means of maintaining legitimacy. The article explores the complexities of Tausert's rule, including her attempts to consolidate power, overcome the influence of the powerful Theban priesthood, and the challenges she faced as a female ruler during uncertain times. Methods.The methods of textological and critical analysis were used in the work with sources, and the translation of Egyptian hieroglyphic texts into Ukrainian was also carried out. Through a comparative analysis of the reigns of Hatshepsut and Tausert, we can understand the broader socio-political dynamics of Ancient Egypt, the shifting structures of power, religious policies, and society's attitudes towards gender roles. Conclutions. The result of these research is the creation of new hypotheses regarding the interpretation of the phenomenon of the reign of female pharaohs in Ancient Egypt. This allows a comprehensive consideration and understanding of an important aspect of the legitimation of power during the crisis periods of the political history of Ancient Egypt. DOI: https://doi.org/10.17721/1728-2640.2023.156.1

Вступ. Розглянуто феномен правління жінок-фараонів у Стародавньому Єгипті із зосередженням на царюванні Хатшепсут і Таусерт, доба Нового царства. Дослідження заглиблюється в історичний контекст, культурне значення та особливості легітимації влади під час їх правління. Аналізуючи першоджерела, включаючи написи, статуї та археологічні пам’ятки, це дослідження має на меті висвітлити унікальні обставини, які дали змогу цим жінкам зійти на престол у суспільстві, де традиційно домінували чоловіки. Прихід до влади цариці Хатшепсут, XVIII династія, суперечив загальноприйнятим очікуванням, що вимагало використання різних додаткових інструментів для легітимації влади: прийняття чоловічих образів, підкреслення божественного походження, широка програма будівництва, військово-торговельні експедиції тощо. Згодом подібне зробить цариця Таусерт, XIX династія, що правила у період політичних потрясінь і занепаду царської влади. Царювання Таусерт є контрастним прикладом, який характеризується акцентом уваги на її зв'язку зі своїм померлим чоловіком, Сеті II, як засобом підтримки легітимності. Також досліджено складність правління Таусерт, зокрема її спроби консолідувати владу, подолати вплив могутнього фіванського жрецтва та виклики, з якими вона стикнулася як жінка-правитель у часи невизначеності. Методи. У роботі з джерелами було використано методи текстологічного та критичного аналізу, здійснено також переклад єгипетських ієрогліфічних текстів українською мовою. Завдяки порівняльному аналізу правління Хатшепсут і Таусерт ми можемо зрозуміти ширшу соціально-політичну динаміку Стародавнього Єгипту, зміну структур влади, релігійної політики та ставлення суспільства до гендерних ролей. Висновки. Результатом дослідження є створення нових гіпотез щодо трактування феномену правління жінок-фараонів у Стародавньому Єгипті.  Це дозволяє всебічно розглянути та зрозуміти важливий аспект легітимації влади під час кризових періодів політичної історії Стародавнього Єгипту. DOI: https://doi.org/10.17721/1728-2640.2023.156.1
Феномен правління жінок-фараонів Хатшепсут та Таусерт: легітимація влади
Keywords: Стародавній Єгипет; Хатшепсут; Таусерт; цариця; культ Амона; жінка-фараон.; ФЕНОМЕН ПРАВЛІННЯ ЖІНОК-ФАРАОНІВ ХАТШЕПСУТ ТА ТАУСЕРТ. ЛЕГІТИМАЦІЯ ВЛАДИ